The role of rural Indian women in livestock production - Kennady, Vijayalakshmy; Chakraborty, Sharmistha; Biswal, Jyotsnarani; Rahman, Habibar (European Open Science Publishing, 2023)
India is an agriculturally based nation, and a significant portion of its livestock sector is controlled by women. Women have a lot of options to increase their income by working in the livestock sector. Livestock provides meat, milk, eggs, and other food products, which are generally considered key assets for rural livelihood, that are dietary staples for population. For the women's livelihood and to help ensure the food security of the household, livestock is a crucial non-land productive asset. The tiny, marginal, and landless farmers in rural areas are the owners of more than 70% of the livestock. Compared to male workers, self-employed women are more likely to work in livestock production. Women add value and market the majority of animal farming activities, including fodder collection, feeding, watering, health care, animal management, milking, and household-level processing. Although rural women have a significant role in livestock management activities, however, their participation is low in certain decision-making activities. The present review elaborates in detail on the contribution of women in livestock management activities, different constraints faced by them in the livestock sector, and different areas where successful interventions can be undertaken to address the challenges faced by women in the livestock sector.